A single-layer urban canopy model with transmissive radiation exchange between trees and street canyons. (15th March 2021) - Wang, Chenghao; Wang, Zhi-Hua; Ryu, Young-Hee
Abstract: Urban trees are one of the most effective strategies to mitigate excessive heat stress in cities. To understand the underlying mechanisms of their cooling effect and to assess their use in urban planning, the accurate simulation of how trees interact with the ambient built environment is critical and imperative. However, the representation of urban trees in existing urban canopy models (in particular the single-layer ones) remains oversimplified. Here we develop a new Monte Carlo ray tracing method to explicitly resolve the canopy transmittance and evaluate its impact on radiative view factors between trees and regular building facets. The new method is highly accurate in reproducing analytical solutions. Sensitivity tests of radiative view factors suggest the importance of canopy transmittance in changing the radiation exchange. We then incorporate the ray tracing algorithm into the new version of the Arizona State University (ASU) Single-Layer Urban Canopy Model (ASLUM v3.1). In addition to radiation transmittance, ASLUM v3.1 explicitly resolves the radiative shading, evapotranspiration, and root water uptake of urban trees in street canyons, with significantly improved performance in predictions (especially latent heat flux) when compared to previous versions. We further apply ASLUM v3.1 to evaluate the impacts of trees with varying characteristics on urban radiation exchange and turbulent heat fluxes. Results show that urban trees reduce the net radiation of ground and wall as well as the daytime temperature via shading and transpiration, but may slightly warm the nighttime street canyons through radiative trapping effect. Graphical abstract: Image 1 Highlights: We develop a new stochastic method to include canopy transmittance in view factors. Sensitivity of view factors to urban geometries and transmittance is evaluated. The new urban canopy model with tree modeling outperforms its previous versions. Radiation exchange and cooling effect of trees depend on foliage characteristics.